Prescribing trends in treatment-resistant schizophrenia. Issue 4 (2nd October 2017) - Görmez, Aynur; Kurtulmuş, Ayşe; Tuncer, Can; Çıtak, Serhat
ABSTRACT: Objectives : Schizophrenia is a common mental health condition associated with significant morbidity and excess early mortality. Treatment-resistant schizophrenia (TRS) occurs in about one in three patients diagnosed with schizophrenia. The aim of this study was to identify attitudes of a nationally representative sample of psychiatrists towards pharmacotherapy of patients with TRS, the potential factors related to their choice of various regimens, and to investigate the clinical outcomes of different methods employed. Methods : Psychiatrists were contacted through national e-groups and various psychiatry conventions. They provided information about their professional and demographic characteristics. They were asked to describe clinical and demographic characteristics of an adult patient with TRS under their care for at least 3 months. They reported on the medication change they made and the effect of this intervention on the positive symptoms and functioning of the patient. Results : Among the 207 patients reported on, only 28.7% were on monotherapy for TRS immediately before the change in medication. With the change made in treatment regime, 40.1% were switched to a different antipsychotic agent as monotherapy, 40.6% received combination therapy with two or more antipsychotic agents, 1.4% received high-dose antipsychotics, and 4.8% had augmentation with antidepressants or mood stabilizers. 13.1% psychiatrists employed more than one method. Of the whole sample, 48.3% were put on clozapine either as monotherapy or with other medications. The monotherapy and combination groups were compared in terms of characteristics of patients and prescribers, which revealed no significant difference ( p  > .05). There was also no difference found on the outcome variables of two groups ( p  > .05). Conclusions : Although polypharmacy was found to be a common practice, there seemed to be a comparably good ratio of clozapine utilization and of attempts of switching to monotherapy among the prescribers. There were no significant patient- or prescriber-related factors in relation to preference of treatment regimens, which need further investigation on larger samples.